Study of antioxidant properties of the dry residue of jellyfish Rhizostoma pulmo - Diachkov, Mykhailo; Ivanchenko, Dmytro (Problems of Environmental Biotechnology, 2021)
The antioxidant activity (AOA) of the dry residue of jellyfish Rhizostoma pulmo was investigated using in vitro method with DPPH reagent, in different concentrations and solvents. The obtained results showed the presence of dose-dependent antiradical activity of the extract from the dry residue of jellyfish.